TINJAUAN NORMATIF TERHADAP TINDAK PIDANA ILLEGAL FISHING OLEH WARGA NEGARA ASING (Studi Kasus Putusan Mahkamah Agung No.131.K/Pid.Sus/2014) - Sunarto S.H., M.H. (JURNAL ILMIAH HUKUM DAN DINAMIKA MASYARAKAT, 2016)
That criminal prosecution against Illegal Fishing in the Supreme Court of No.131.K / PID.SUS / 2014 stem from criminal acts, the indictment: Nguyen Phan SY arrests Fish in Indonesia Sea region does not have License Arrest (original) Fish abuse Article 92 of Law Number 45 year 2009 on changes to Law No. 31 year 2004 on Fisheries, shall be punished with imprisonment of 8 years, a maximum fine of Rp. 1.5 billion. The defendant does not have a fishing permit (SIPI) in violation of Article 93 paragraph (2) of Law No. 45 of 2009 on the Amendment of Act No. 31 of 2004 on Fisheries, sentenced to 6 years, a maximum fine of Rp. 20 billion. Consideration of the use of judges in deciding where the offense is considered legally rests on three (3) counts as the article alleged. Non Juridical consideration is the absence of the defendant simplify things, and burden the defendant Nguyen Phan Sy.